Social Memory and Violence in Soccer: Institutionalized Memories in the Press of Medellin, Colombia - Vélez Maya, Margarita María; Arboleda Ariza, Juan Carlos (Pensando Psicología, 2016)
Introduction: This article is the product of the research project “Social Memory Constructions around Soccer-Related Violence: Discourse Analysis in the Newspaper El Colombiano from Medellin.” Objective: The purpose of the research was to understand the constructions of social memory of soccer violence in the press. Methodology: This study was conducted from a qualitative approach, through discourse analysis, whereby discursive strategies and functions of narratives that are used to refer to the phenomenon are explored. The analysis of 188 journalistic articles produced by the newspaper El Colombiano in the period between 2010 and 2015 was conducted. Results: Crystallized memories of violence in soccer are presented, which are historic narrations, such as the memory of an ideal past without violence; the beginnings of violence: the 5-1 result of Colombia vs. Argentina and the murder of Andres Escobar; and the establishment of violence: the relationship of drug trafficking with soccer and the influence of hooligans. Conclusions: It is possible to argue that the press has a special place in the institutionalization and circulation of memories regarding soccer and violence.